2007
DOI: 10.1136/ard.2007.076232
|View full text |Cite
|
Sign up to set email alerts
|

Gout in the UK and Germany: prevalence, comorbidities and management in general practice 2000-2005

Abstract: Objective:To investigate and compare the prevalence, comorbidities and management of gout in practice in the UK and Germany.Methods:A retrospective analysis of patients with gout, identified through the records of 2.5 million patients in UK general practices and 2.4 million patients attending GPs or internists in Germany, using the IMS Disease Analyzer.Results:The prevalence of gout was 1.4% in the UK and Germany. Obesity was the most common comorbidity in the UK (27.7%), but in Germany the most common comorbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
281
4
27

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 450 publications
(337 citation statements)
references
References 30 publications
25
281
4
27
Order By: Relevance
“…As compared with results in the UK, which found significant differences by living area (4), we found no significant difference in prevalence across areas of France. Our overall prevalence estimate was of the same order as that reported for Italy (3) but lower than that reported for other European countries (4,(16)(17)(18), the US (2), and countries in Asia and the Pacific (19)(20)(21)(22)(23)(24).…”
Section: Discussionsupporting
confidence: 49%
“…As compared with results in the UK, which found significant differences by living area (4), we found no significant difference in prevalence across areas of France. Our overall prevalence estimate was of the same order as that reported for Italy (3) but lower than that reported for other European countries (4,(16)(17)(18), the US (2), and countries in Asia and the Pacific (19)(20)(21)(22)(23)(24).…”
Section: Discussionsupporting
confidence: 49%
“…7 It is higher than longitudinal databases of selected populations in the UK (1.4%), US (3.9%) and Italy (0.91%). 10,11,13 The only comparable Australian study is a 2002 Indigenous Australian study 18 , for which self-reported gout was confirmed by clinical examination and investigation, which found an overall prevalence of 3.8% (males 9%, females 0.7%). From a participant self-reported population survey from the Australian Bureau of Statistics (1997Statistics ( -1999, the prevalence of gout was 1.7%.…”
Section: Discussionmentioning
confidence: 99%
“…11 Obesity, hypertension, dyslipidaemia and chronic renal failure have consistently been identified to be increased in the gout population. 8,10,11,12,13 The association of diabetes mellitus and a current smoking history are less well defined with some studies finding them to be less prevalent in people with gout. 2,10,12 To date health related quality of life (HRQoL) has not been extensively assessed in gout trials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations